Old Slavic Sermon Language: The Extraordinary Nature of Verb Morphology in Cyril Turovskij’s Homilies - Zholobov, Oleg F. (Slověne, 2017)
The article’s subject matter—verbs functioning in the sermons of the Old Russian church writer Cyril Turovskij (second half of the 12th century)—is considered in details for the first time on the basis of the earliest source, Tolstovskij Sbornik (second half of the 13th century). Since Cyril’s sermons were addressed to a wide range of listeners and readers they had to be based on intelligible and simple language forms that also preserved a connection with literary standards. This manifested itself in the significant Russification of the preaching language. The article describes the following features of the language of Cyril’s sermons: the earliest and widespread usage of “praesens historicum”; the exclusive usage of aorist forms with additional endings (načętъ type); the special functional and syntactic nature of the aorist rěšę; the unusually wide usage of 2 Sg. aorist and imperfect forms; the usage of perfective imperfect forms and imperfects with additional endings; the prospective future tense and modal functioning of the paraphrastic forms with the auxiliary verb xoščè; special cases of 1 Pl. imperatives usage; the special character of the reflexive enclitic sę; and the extraordinary distribution of periphrastic preterits forms. Some similarity of verbs functioning in Cyril’s homilies and The Tale of Igor’s Campaign is detected as well as in the original Chronicle, early Old Russian translations, and Paroemiarion.